Los virus en el cine: entre la ficción y la pedagogía (Ensayos) - Brito Alvarado, Leonardo Xavier (2023)
Without a doubt, the COVID-19 pandemic has brought science fiction back to the political and social debate. The stories present in science fiction, which at first were related to unlikely situations, and today their narrations, in many cases, are located in the pedagogical sphere that explains about possible apocalyptic scenarios of the end of humanity, (pandemics, invasion alien, revolution of the machines, among others are the main stories,) his speeches interweave the fantastic and scientific with the intention of creating an accessible and spectacular language for the majority of the population, which seeks in these stories the causes, consequences and solutions to apocalyptic scenarios that put life on the planet at risk. This essay is based first of all on a reading from the Social Sciences, and later on the analysis of films related to this genre, which starts from the perspective of Enrico Quarantelli who exposes a sociology of disaster. In this way, it is intended to interweave fiction cinema with a pedagogical discourse aimed at reflecting on the various social, economic, political and cultural situations that cause scenarios related to pandemics.